Integrated improvisation instruction into the daily jazz band rehearsal - Partin, Ryan (Kansas State University, 2024)
The purpose of this master’s project was to develop and implement daily improvisation instruction in the high school jazz ensemble rehearsal. I consider myself a competent jazz musician, but up until this school year, I did not have any structured improvisation lessons in place. This newly developed curriculum presents the topic of jazz improvisation in a logical and clearly sequenced design that starts with the most basic principles of listening and melody construction, giving the students the foundation upon which to build their knowledge and facility as improvisors. The primary focus is on utilizing articulations and rhythmic ideas that exemplify the style, with a secondary focus on note selection. To further develop their sense of time and style, students listened and responded to various famous jazz solos in several styles, echoed rhythms that were demonstrated by the instructor, and composed several short musical ideas, or licks. At the conclusion of the project, each student performed one chorus of an improvised solo and critiqued their classmate’s improvisation based on the provided rubric. Over the course of my Master’s Program at Kansas State University, I further honed my ability to develop a curriculum that is organized in a natural sequence of learning and is well thought out for the entire year. I utilized the backward design process of starting with desired outcomes first, a process I learned while taking the course Curriculum Development and Learning Assessment at KSU last summer. I also learned to create adequate assessment tools that inform my decisions on further curriculum refinement. The process of developing program goals, course goals, and assessment tools has further refined my understanding of effective course design and will only increase my impact as an educator. Though my master’s project was focused on one aspect of jazz ensemble rehearsal, I plan to use what I have learned about curriculum development to further refine all aspects of my teaching. Another area of growth that I experienced during my time at KSU is my ability to confidently access and interpret research in music education. I now have a plethora of resources at my disposal, and I can identify and implement new practices in my classroom that are backed by empirical evidence. Based on my newfound knowledge in educational research, I created an action research project that examined the relationship between singing tonal rhythm patterns and its effect on intonation of middle school band students. I enjoyed the process of creating the research project and I will most certainly create more action research projects throughout my career. My time at Kansas State University has made me a more effective music educator and has equipped me with the skills and knowledge to provide an excellent music education for my students.
Keywords: Music education; Jazz; Improvisation; Music curriculum; Band